Coastal phytoplankton responses to atmospheric deposition during summer - Zhou, Weiwen; Li, Qian P.; Wu, Zhengchao (Limnology and oceanography, 2021)
The northern South China Sea is subject to an increasing influence of aerosol loading, particularly over the past decades owing to the fast economic growth of mainland China. To study the response of the coastal phytoplankton community to atmospheric deposition, we performed onboard microcosm experiments at various coastal regions of the northern South China Sea, including a river plume zone and the two major upwelling zones. We found that the addition of aerosol and rainwater significantly increased the micro-phytoplankton size-fraction by 2.3–5.4-folds regardless of the type of preexisting nutrient limitation in the phytoplankton community. There were three types of distinct responses to the manipulation additions observed: positive, negligible, or even negative effects. A significant inhibition effect (27–74% decrease) in the Qiongdong upwelling zone could be attributed to elevated metal toxicity on the phytoplankton community seeding from the subsurface after it had been brought up to the surface due to an outcrop of the thermocline. While Prochlorococcus growth was uniformly inhibited by the additions, both positive and negative effects were observed for the remainder of the picoplankton community. P-limited Synechococcus was stimulated by aerosol and rainwater additions (1.2–-2.8-folds increase), whereas N-limited Synechococcus was inhibited (decreased by 9–28%). Our results suggest that coastal phytoplankton responses to atmospheric depositions are regulated by both the fertilizing effects of aerosol nutrients and the toxic effects of aerosol metals. Our findings highlight the critical role of atmospheric depositions on spatial change of phytoplankton biomass and community structure in the coastal ocean, which could greatly affect ecosystem dynamics and biogeochemical cycles of the shelf sea.